An ontology for mapping cerebral death - Silva, António João Oliveira (2017)
Brain death is one of the most serious diagnoses that can be diagnosed in a patient. The possibility to detect it before its happening is one of the possible steps for the prevention of this event. The x-rays – Computed Tomography scans, are a very important test for the detection of this diagnosis. This paper proposes the use of an ontology on the registration of x-rays made to patients. This work was performed through the data provided by the Centro Hospitalar do Porto - Hospital de Santo António. The ontology was used based on an analysis made to the data and with the use of a dictionary developed in the same analysis. Finally, we added to the ontology the types of patients with brain death that were discov ered in a previous work that used the dictionary that is present in this ontology.